2009
DOI: 10.1897/08-286r.1
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of environmental pollutants (nickel, chlorpyrifos) and temperature on the ground beetle,Pterostichus oblongopunctatus(Coleoptera: Carabidae)

Abstract: Terrestrial organisms in the field often are exposed to a combination of stress factors of various origins, but little is known about interactions between different types of stressors. In the present study, we demonstrate the results of a study on interactions between Ni, chlorpyrifos (CPF), and temperature in the ground beetle, Pterostichus oblongopunctatus. The results revealed that all factors, and their interactions, influenced life-cycle parameters of the beetles (survival and reproduction). Significant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Life history endpoints may respond differently to the same stressor or a combination of stressors. For example, Bednarska et al ( 2009 ) found that the reproduction of adult ground beetles was most sensitive to nickel concentrations at low and high temperatures (10 and 25 °C), but the survival was less affected by the combined effect of Ni and chlorpyriphos at both temperatures. Furthermore, Laskowski et al ( 2010 ) conducted a meta-analysis on the interactions between toxic chemicals and natural environmental factors across a range of vertebrates and invertebrates species (including metals and D. magna ), finding that the effects of toxicants on organisms may differ depending on external factors.…”
Section: Discussionmentioning
confidence: 99%
“…Life history endpoints may respond differently to the same stressor or a combination of stressors. For example, Bednarska et al ( 2009 ) found that the reproduction of adult ground beetles was most sensitive to nickel concentrations at low and high temperatures (10 and 25 °C), but the survival was less affected by the combined effect of Ni and chlorpyriphos at both temperatures. Furthermore, Laskowski et al ( 2010 ) conducted a meta-analysis on the interactions between toxic chemicals and natural environmental factors across a range of vertebrates and invertebrates species (including metals and D. magna ), finding that the effects of toxicants on organisms may differ depending on external factors.…”
Section: Discussionmentioning
confidence: 99%
“…As such, if the interaction between chemicals is low, the additional effects of environmental factors on each component of the mixture is likely to become the main source of uncertainty, being thus the main driver for potential deviations to the predicted toxicity. More studies are however needed to confirm this hypothesis since the effects of natural environmental factors on pesticide mixtures, or mixtures of xenobiotics in general, are still largely unknown (Bednarska et al, 2009;Laskowski et al, 2010). Given the impossibility of assessing every single pesticide under all exposure scenarios, a critical step would have to be the prioritization of the most relevant conditions to be assessed for a particular compound.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative evidence that different environmental conditions and chemical stressors can interact, influencing each other's effects on soil biota has been pushing ecotoxicologists to assess increasingly complex scenarios (van Gestel and van Diepen, 1997;Bednarska et al, 2009;Cardoso et al, 2014;Lima et al, 2014;Ferreira et al, 2015). This situation has been prompted by the growing awareness that studies currently supporting environmental risk assessments may not be representative of realistic exposures to xenobiotics since they neglect the simultaneous occurrence of mulhttp://dx.doi.org/10.1016/j.chemosphere.2015.10.034 0045-6535/© 2015 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%